A functional M196R polymorphism of tumour necrosis factor receptor type 2 is associated with systemic lupus erythematosus: a case–control study and a meta-analysis. (6th October 2006) - Horiuchi, Takahiko; Kiyohara, Chikako; Tsukamoto, Hiroshi; Sawabe, Takuya; Furugo, Isao; Yoshizawa, Seiji; Ueda, Akira; Tada, Yoshifumi; Nakamura, Tadashi; Kimoto, Yasutaka; Mitoma, Hiroki; Harashima, Shinichi; et al.
Abstract : Objectives: To perform a case–control study of a functional M196R polymorphism of tumour necrosis factor receptor type 2 (TNF-RII) in a Japanese population and a meta-analysis of all published reports on the polymorphism to investigate the association of the M196R polymorphism of TNF-RII with systemic lupus erythematosus (SLE). Methods: The functional M196R polymorphism of TNF-RII was genotyped by using polymerase chain reaction combined with the subsequent single-strand conformation polymorphism (PCR—SSCP) analysis for screening, followed by nucleotide sequencing for confirmation. A total of 331 patients and 359 controls were subjected to a case–control study. A meta-analysis of the available case–control studies including all published data as well as our own data was performed to investigate the association of the functional M196R polymorphism of TNF-RII with SLE. Results: Our case–control study did not show any significant association of a functional M196R polymorphism of TNF-RII with SLE, although there was a trend towards association. A meta-analysis of seven case–control studies in eight different ethnic populations including our own showed that 196M/R and 196R/R genotypes combined was significantly associated with an increased risk of SLE (odds ratio (OR) 1.29, 95% confidence interval (CI) 1.04 to 1.60; p = 0.02). Stratification by ethnicity showed a more significant association in Asians, including Japanese, Korean and Vietnamese (OR 1.40, 95% CI 1.10 to 1.78; p = 0.006). The effect of the 196R allele on SLE was not clear in Caucasians. Conclusions: The 196R allele of the functional M196R polymorphism of TNF-RII is a risk factor for SLE, especially in the Asian population.